Clinical and demographic pattern of chronic granulomatous disease (CGD) from a multicenter perspective: Malaysia’s experience over 26 years - Lokman Mohd Noh; Amir Hamzah Abdul Latiff; Intan Hakimah Ismail; Rahim Md Noah; Asrul Abdul Wahab; Intan Juliana Abd. Hamid; Adiratna Mat Ripen; Nasuruddin B. Abdullah; Kamarul Azhar Razali; Norzila Zainudin; Florence Bakon; Long Juan Kok; et al. (Allergy, Asthma & Clinical Immunology, 2021)
Abstract Background A retrospective review of clinical manifestations and demographic pattern of patients diagnosed as chronic granulomatous disease (CGD) from 7 hospitals in Malaysia. An analysis of the available database would establish clinical characteristics, diagnoses and outcome including microbiologic pattern. Studying the demography allows us to document the occurrence of CGD amongst multiethnic groups and its geographical distribution for Malaysia. Methods Data from the Malaysia Primary Immunodeficiency Network (MyPIN) with cases of CGD diagnosed from 1991 until 2016 were collated and analysed. Results Twenty patients were diagnosed as CGD. Males (N = 13, 65%) outnumber females (N = 7, 35%). CGD is commonest amongst the Malays (65%) followed by the Chinese (15.0%), Indians (10.0%) and natives of Borneo (10.0%), reflecting the ethnic composition of the country. The mean age of diagnosis was 3.7 years. There was a positive family history in 40% of the cases. Abscess was the main presenting feature in 16 patients (80%) with one involving the brain. Pneumonia occurred in 10 (50%) and one with complicated bronchiectasis. Catalase-positive bacteria were the most commonly isolated pathogen with Chromobacterium violaceum predominating (N = 5, 25%) with consequent high mortality (N = 4, 80%). All CGD patients with C. violaceum infection displayed CD4 + (T helper cells) lymphopenia. Conclusion This study has shown CGD occurs in the major ethnic groups of Malaysia. To the best of our knowledge, this is the first and the largest series of chronic granulomatous disease in South East Asia which may be reflective of similar clinical pattern in the region. C. violaceum infection is associated with a higher mortality in CGD patients in Malaysia. All the CGD patients with C. violaceum infection in this patient series displayed CD4 + (T helper) lymphopenia. We recorded rare clinical manifestation of CGD viz. brain abscess and bronchiectasis.